Distribution of CFCs and its tracer study in the Chukchi Sea and adjacent areas - Deng, Yongzhi; Sun, Na; Zheng, Shulan; Zhuang, Chuanling; Li, Wenquan; 李文权 (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2012)
During the second Chinese Arctic Scientific Expedition (CHINARE 2003. 2003.07 similar to 2003.09), chlorofluorocarbons (CFCs) were measured from water samples collected from 26 stations in the Chukchi Sea and adjacent areas. CFCs data indicated that they had not reach saturation in surface waters. The 170 degrees W section distribution of CFCs and the thermohaline characteristics in the Chukchi Sea confirmed that there was an inflow of Pacific Ocean water into the Arctic Ocean via the Central Channel. There are three main new results. The first, there were two sources of freshwater, the Alaskan Coastal Water (ACW) and sea ice melt water, in the shallower than 20 m seawater. The second, the water mass at station BSO9A was ACW, and that stations BSO6A and BSO7A were likely to be a place of confluence for ACW and Bering Sea shelf Water (BSW), or for ACW, BSW and Anadyr Water (AW) water masses. The third, the ACW almost flowed along the coast, and so it had less influence on the more distant offshore stations. National Natural Science Foundation of China